DURABILITY OF HRS-WC MIX WITH ANTISTRIPPING WETFIX-BE AND FLY ASH FILLER - Siti Alpiah (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
Damage to flexible pavement can be caused by asphalt, which has weaknesses due to its low viscosity and resistance to heat, radiation, and oxidation. Furthermore, road damage is also caused by water ingress into the aggregate pores, which typically occurs during rain, when the pavement is traversed before it is sufficiently strong, or because the asphalt does not evenly cover the rock. Therefore, special considerations are needed when designing asphalt mixtures, including improving their quality. One way to do this is by modifying them with additives that are expected to increase the asphalt's bonding energy to the rock. One additive that can reduce peeling damage due to sunburn is Wetfix-Be, a liquid that works to improve the asphalt's bonding properties to the rock. The purpose of this study was to determine the effect of Wetfix-Be on fly ash filler and cement. This study tested the durability of the HRS-WC mixture and varied soaking times (30 minutes, 24 hours, and 48 hours). Furthermore, Wetfix-Be was added at 0.2%-0.5%. The mixture design varied in asphalt content from 5.5%, 6%, 6.5%, and 7%. The method used in this study was the Marshall Test, which examines the stability and flow, as well as the density and pore size of the resulting solid mixture. The test results obtained for cement filler with an optimum asphalt content of 6.5% and an optimum wetfix-be content of 0.31%, while for fly ash filler with an optimum asphalt content of 6.4% and an optimum wetfix-be content of 0.41%. The Residual Strength Index (SIKS) was >80% for both fillers. The fly ash filler achieved higher values than cement after 24 hours (91.8%) and 48 hours (91.39%).